The MYB transcription factor Baymax1 plays a critical role in rice male fertility - Xiang, Xiao-Jiao; Sun, Lian-Ping; Yu, Ping; Yang, Zheng-Fu; Zhang, Pei-Pei; Zhang, Ying-Xin; Wu, Wei-Xun; Chen, Dai-Bo; Zhan, Xiao-Deng; Khan, Riaz-Muhammad; Abbas, Adil; Cheng, Shi-Hua; et al. (Theoretical and applied genetics, 2021)
Key message Rice male fertility gene Baymax1 , isolated through map-based cloning, encodes a MYB transcription factor and is essential for rice tapetum and microspore development. The mining and characterization of male fertility gene will provide theoretical and material basis for future rice production. In Arabidopsis , the development of male organ (namely anther), usually involves the coordination between MYB (v-myb avian myeloblastosis viral oncogene homolog) and bHLH (basic helix-loop-helix) members. However, the role of MYB proteins in rice anther development remains poorly understood. In this study, we isolated and characterized a male sterile mutant (with normal vegetative growth) of Baymax1 ( BM1 ), which encodes a MYB protein. The bm1 mutant exhibited slightly lagging meiosis, aborted transition of the tapetum to a secretory type, premature tapetal degeneration, and abnormal pollen exine formation, leading to ultimately lacks of visible pollens in the mature white anthers. Map-based cloning, complementation and targeted mutagenesis using CRISPR/Cas9 technology demonstrated that the mutated LOC_Os04g39470 is the causal gene in bm1 . BM1 is preferentially expressed in rice anthers from stage 5 to stage 10. Phylogenetic analysis indicated that rice BM1 and its homologs in millet, maize, rape, cabbage, and pigeonpea are evolutionarily conserved. BM1 can physically interacts with bHLH protein TIP2, EAT1, and PHD (plant homeodomain)-finger member TIP3, respectively. Moreover, BM1 affects the expression of several known genes related to tapetum and microspore development. Collectively, our results suggest that BM1 is one of key regulators for rice male fertility and may serve as a potential target for rice male-sterile line breeding and hybrid seed production.